2014
DOI: 10.1038/ncomms5410
|View full text |Cite|
|
Sign up to set email alerts
|

The adipokine Retnla modulates cholesterol homeostasis in hyperlipidemic mice

Abstract: Hyperlipidemia is a well-recognized risk factor for atherosclerosis and can be regulated by adipokines. Expression of the adipokine resistin-like molecule alpha (Retnla) is regulated by food intake; whether Retnla has a role in the pathogenesis of hyperlipidemia and atherosclerosis is unknown. Here we report that Retnla has a cholesterol-lowering effect and protects against atherosclerosis in low-density lipoprotein receptor-deficient mice. On a high-fat diet, Retnla deficiency promotes hypercholesterolaemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 70 publications
(99 reference statements)
0
37
0
Order By: Relevance
“…Retnla −/− mice show faster glucose clearance in GTT in mice with dextran sodium sulfate-induced colitis (Munitz et al, 2009). Furthermore, RELMα deficiency in Ldlr − / − atherosclerotic mice results in hypercholesterolemia, while its overexpression in WT animals reduces serum cholesterol and directly induces bile acid synthases Cyp7a1 and Cyp8b1 in the liver (Lee et al, 2014). Our results of the elevated serum cholesterol and reduced hepatic Cyp8b1 expression in CD301b + MNP-depleted mice are thus consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Retnla −/− mice show faster glucose clearance in GTT in mice with dextran sodium sulfate-induced colitis (Munitz et al, 2009). Furthermore, RELMα deficiency in Ldlr − / − atherosclerotic mice results in hypercholesterolemia, while its overexpression in WT animals reduces serum cholesterol and directly induces bile acid synthases Cyp7a1 and Cyp8b1 in the liver (Lee et al, 2014). Our results of the elevated serum cholesterol and reduced hepatic Cyp8b1 expression in CD301b + MNP-depleted mice are thus consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cox6a2 is a nuclear gene that encodes one of 13 subunits of the mitochondrial cytochrome c oxidase complex that if deficient in mice results in ROS overproduction in skeletal muscle (70). Retnla encodes an adipokine with cholesterol catabolism properties (71) raising the possibility of an anti-inflammatory-like response during cataract development in the Lop/+ lens. Sqstm1 encodes a stress-induced scaffold protein (p62) with multiple domains that act as a signaling hub for diverse cellular events including, NF-kB activation, mTORC1 activation, selective autophagy, and Nrf2 signaling (72).…”
Section: Discussionmentioning
confidence: 99%
“…New studies have identified a critical metabolic function for RELMα in protection against atherosclerosis in both high fat diet fed mice and LDL receptor deficient mice [84]. Mice lacking the LDL receptor ( ldlr −/− ) cannot efficiently remove circulating LDL, leading to increased formation of atherosclerotic plaques in the context of high fat diet.…”
Section: Resistin and Resistin-like Moleculesmentioning
confidence: 99%